(untitled) (Spagna contemporanea. Rivista semestrale di storia, cultura, istituzioni, 1998)
Monarquía y cambio democrático: reflexión sobre un debate historiográfico The article is a reflection on the relationships between both Don Juan de Borbón and Don Juan Carlos and the transition to democracy process occurred after Franco’s death. It gives an evaluation of the most important recent publications on both characters, and tackles such essential matters as Juan de Borbón’s ideological evolution and his plans for a monarchy following Franco’s dictator-ship; Prince Juan Carlos’ projects for democratic change and his role in the change’s process occurred during his reign; and finally Franco’s stance towards monarchy and whether he foresaw his régime being terminated by his successor.